2014
DOI: 10.1017/thg.2014.48
|View full text |Cite
|
Sign up to set email alerts
|

Late Prematurity in Twins: A Polish Multicenter Study

Abstract: The study aimed at investigating the impact of late prematurity (LPT) on neonatal outcome in twins and neonatal morbidity and mortality within LPT with regard to the completed weeks of gestation. The study was conducted in six tertiary obstetric departments from different provinces of Poland (Warsaw, Lublin, Poznan, Wroclaw, Bytom). It included 465 twin deliveries in the above centers in 2012. A comparative analysis of maternal factors, the course of pregnancy and delivery and neonatal outcome between LPT (34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…It has been confirmed that the incidence of twin pregnancies has doubled over the course of the last fifty years, meaning that twins comprise almost 3% of all births in countries such as France or the USA [ 4 , 5 ]. According to a report in the Demographic Yearbook of Poland 2019, 2.5% of all births during the previous year originated from twin pregnancy [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the incidence of twin pregnancies has doubled over the course of the last fifty years, meaning that twins comprise almost 3% of all births in countries such as France or the USA [ 4 , 5 ]. According to a report in the Demographic Yearbook of Poland 2019, 2.5% of all births during the previous year originated from twin pregnancy [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de todos os esforços e avanços da medicina perinatal, a taxa de mortalidade nas gestações múltiplas permanece mais alta do que a observada em gestações únicas 2 . Sendo assim, um desafio da prática obstétrica é prevenir a prematuridade e, para tal, várias estratégias estão sendo adotadas, como o uso profilático da progesterona exógena [4][5][6] .…”
unclassified
“…Undeterred, today we are honored to be helping with the organization of the first Twins Congress in the region and, along with the abstracts of the conference, presenting a diverse set of articles on twin research from CEE and Hungary. First, Pári (2014) presents a historical and demographic overview of twin births in Hungary, followed by Kosinska-Kaczynska et al's (2014) Polish multicentric study on late prematurity in twins. Next is Hegedűs et al's (2014) sociological assessment of what advantages being a twin brings, followed by Molnár et al's (2014) case study of multiple valve disease found in triplets.…”
mentioning
confidence: 99%